Sintesis dan Karakterisasi Struktur dan Sifat Magnet Nanokomposit Fe3O4@PEG:ZnO - Astuti Astuti; ihda khaira; syukri Arief; Sri Rahayu Alfitri Usna (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2022)
Fe3O4@PEG:ZnO nanocomposites were synthesized by the coprecipitation method with various of the samples were Fe3O4, Fe3O4@ZnO (1:1), Fe3O4@PEG: ZnO (1:2), and Fe3O4@ PEG: ZnO (1:3). The samples were synthesized with variation in the concentration of ZnO to Fe3O4. The concentration ratio of (Fe3O4:ZnO) were (1:1), (1:2), and (1:3). In addition, polyethylene glycol (PEG) is also used to prevent the agglomeration of Fe3O4. Sample characterization was carried out using X-Ray Diffraction (XRD), Transmission Electron Microscope (TEM), Fourier Transform Infrared (FTIR), Particle Size Analyzer (PSA), and vibrating Sample Magnetometer (VSM). The XRD patterns show that the sample is composed of Fe3O4phase and ZnO phase with crystal structure cubic and wurtzite respectively. The TEM image shows the formation of a core-shell structure where PEG: ZnO is the shell and Fe3O4 is the core. From the FTIR results, there are C-O and C-C bonds which indicate the formation of PEG, Fe-O bonds indicate the formation of Fe3O4 and Zn-O bonds indicate the formation of ZnO. Characterization with PSA obtained particle sizes of 33 nm, 23 nm, and 16 nm with particle size distributions of 25%, 50%, and 75% so that the average particle size is 24 nm. The VSM results show that Fe3O4@PEG: ZnO (1:2) nanocomposite has a high magnetic saturation of 66.58 emu/g, with superparamagnetic properties, which has the potential to be developed as a bioimaging material.